2013
DOI: 10.1017/s0014479712001330
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Tillage and Nutrient Management Practices for Sustainable Yields, Profitability and Energy Use Efficiency for Rice-Based Cropping System in Different Soils and Agro-Climatic Conditions

Abstract: Long-term tillage and fertilizer experiments were conducted in rice in kharif followed by lentil in dry subhumid Inceptisols at Varanasi and Faizabad; horse gram at Phulbani and linseed at Ranchi in moist subhumid Alfisols in rabi during 2001 to 2010. The study was conducted to assess the effect of conventional tillage (CT), low tillage + interculture (LT1) and low tillage + herbicide (LT2) together with 100% N (organic) (F1), 50% N (organic) + 50% N (inorganic) (F2) and 100% N (inorganic) (F3) on productivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…In the last decades, the transformation to industrial society determined changes in agricultural practices from their basic function of providing food and labour to becoming a supplier of raw materials in agro-industrial and agri-business systems. However, the industrial agriculture system is heavily dependent on fossil fuels and synthetic agrochemicals as the main source of energy and material to manage the cultivated plant in the agro-ecosystems [1]. In addition, it is managed by large-scale monoculture and cultivation based on intensive soil tillage operations.…”
Section: Introductionmentioning
confidence: 99%
“…In the last decades, the transformation to industrial society determined changes in agricultural practices from their basic function of providing food and labour to becoming a supplier of raw materials in agro-industrial and agri-business systems. However, the industrial agriculture system is heavily dependent on fossil fuels and synthetic agrochemicals as the main source of energy and material to manage the cultivated plant in the agro-ecosystems [1]. In addition, it is managed by large-scale monoculture and cultivation based on intensive soil tillage operations.…”
Section: Introductionmentioning
confidence: 99%
“…Besides intercropping, 44.8% of farmers are also currently planting short-duration crops, 44.0% of them use organic fertilizer, 42.8% of them practice minimum tillage, and 37.5% of them adapt their cropping calendar to prevailing weather conditions. Results from previous research studies have shown that farmers need to plant at different dates as a coping strategy to adapt to the erratic pattern of rainfall, and in cases where their crops repeatedly failed, they need to replant their fields many times depending on the commonly forecast weather indicators [26] and the use of weed residues to replenish soil fertility through minimum soil tillage practices and reduces surface runoff and erosion [27]. In addition, 32.2% of the farmers are using/ planting drought-resistant crops, 20.2% practicing in-field rainwater harvesting, 36.5% are practicing mulching, 16.2% are practicing reduced rates of the application of agrochemicals, 26.0% practice integrated pest management (IPM) and 31.2% practice integrated soil fertility management.…”
Section: Farmers' Knowledge and Use Of Climate-sensitive Agriculturalmentioning
confidence: 99%